Strategy Development for Educational Resource Management of Secondary Schools Under The secondary Educational Service Area Office Kalasin: Strategy Development for Educational Resource Management of Secondary Schools Under The secondary Educational Service Area Office Kalasin - Phonrueangthong, Kusumawadee; Duangchatom, Kritkanok; Phoojomjit, Pongphop (RATANABUTH JOURNAL, 2023)
The objectives of this research were 1) to study the current conditions, desirable conditions and needs assessment for the management of educational resources in secondary schools under the secondary educational service area office Kalasin. and 2) proposed a strategy for educational resource management of secondary schools under the secondary educational service area office Kalasin, The research was divided into 2 phases. Phase 1. Studied the current situation desirable and needs assessment, The target group is 7 experts to examine components and indicators. and a sample of 322 people to study the current conditions, desirable conditions . The research tools were interview forms and questionnaires. The confidence value of the whole version was equal to .94. Phase 2. proposed a strategy for managing the educational resources of secondary schools. The target group is a group of 17 experts in the workshop and a group of 34 experts participating in the public hearing. The research results found that The overall current condition is average at a moderate level. The overall desirable condition was at a high level. Overall needs assessment were PNI Modified = 0.30. The aspect with the highest needs index was educational resource management and planning. followed by management of educational resources in the field of assessment and management of educational resources in operation, respectively. The components of educational resources consisted of 1) Human resource, 2) Money resource, 3) Material resource, and 4) Premise resource. Educational resource management strategies of secondary schools under the secondary educational service area office Kalasin, consists of 4 main strategies, 9 secondary strategies, and 43 strategies at the operational level. And the results of the strategic evaluation in terms of suitability and consistency were at a high average level. The possibility part and overall usefulness were at the highest average level.